GOOD HABITUATION METHODS TO BUILD STUDENTS DISCIPLINE CHARACTER AT MAN SORONG - Syahrul Syahrul; Laili Rohmawati; Masseni Masseni; Dwi Iin Kahina; Evie Syalviana; Muhammad Ali Raja; Muh. Ansar; Hermanto Hermanto; Miftahulfadlik Dabamona (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2026)
Good habituation in school activities refers to activities that are carried out consistently and purposefully to form a good and positive character of students. Good habituation activities can be carried out in the form of school programs, school rules, and daily activities in the classroom. The goal is to form positive patterns of behavior and help learners to develop good and quality character. This study discusses the impact of good habituation on the character of students of MAN Sorong sp 4. Good habituation that is carried out consistently and purposefully can shape the character of students, such as a sense of discipline, responsibility, honesty, hard work, and an unyielding spirit. This research is qualitative research using descriptive research methods. The results showed that good habituation applied in schools had a positive impact on the character of students, on the time discipline indicators obtained 86% with excellent qualifications, then the discipline indicators of enforcing the rules obtained 74.3% with good qualifications, then on the attitude discipline indicators obtained 83% with excellent qualifications, and on the indicators of discipline in worship obtained 87.5% with excellent qualifications. Thus, good habituation needs to be applied consistently and purposefully in schools to form a better character of students so that students become more disciplined, responsible, honest, diligent, and have an unyielding spirit.